Flow and heat transfer analysis on micropolar fluid through a porous medium between a clear and Al2O3−Cu/H2O in conducting field - Tanuja, T. N.; Kavitha, L.; Varma, S. V. K.; Khan, Umair; Sherif, El-Sayed M.; Hassan, Ahmed M.; Pop, Ioan; Sarada, K.; Gill, Harjot Singh (Frontiers in Materials, 2023)
The current study is focused on the flow of micropolar liquid in a saturated permeable medium sandwiched between clear and hybrid nanofluid filled in an inclined channel, with radiation and dissipation effects. Copper and Aluminium oxide nanoparticles is considered along with base (water) fluid. The solution for velocity, micro rotational velocity, and temperature are determined by applying the regular perturbation technique to the dimensionless version of the governing equations. The heat transport rate at the left and right plate is also calculated, as well as shear stress expressed in terms of skin-friction coefficient and Nusselt number. The result obtained for various physical parameters are analyzed through several graphs and tables. Results reveal that an increase in the material parameter of micropolar fluid, the motion of the fluid flow decreases. The heat transport rate is enhanced and the velocity is degraded by the magnetic parameter. The Hybrid nanofluid temperature is greater when compared to clear and binary hybrid nanofluid. This work establishes the mechanisms for heat transport enhancement on micropolar liquid through a porous medium between a clear and hybrid nanofluid in conducting field.